2015
DOI: 10.1039/c5ay00245a
|View full text |Cite
|
Sign up to set email alerts
|

A photoelectrochemical sensor through quenching of photoinduced electrons based on a G-quadruplex/hemin complex

Abstract: A novel label-free photoelectrochemical sensor was fabricated for the detection of K+ based on the electron withdrawal effect of hemin. The decreasing photocurrent from photoinduced electron transfer by a G-quadruplex/hemin complex was utilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…13, the decreasing photocurrent from photoinduced electron transfer by the formation of a G-quadruplex/hemin complex in the presence of K + was utilized as a sensing signal for label-free PEC detection of K + , and a linear relationship of photocurrent intensity versus K + concentration from 0.5 to 10 mM was obtained. 84…”
Section: Detection Of Potassium (K) Ionsmentioning
confidence: 99%
“…13, the decreasing photocurrent from photoinduced electron transfer by the formation of a G-quadruplex/hemin complex in the presence of K + was utilized as a sensing signal for label-free PEC detection of K + , and a linear relationship of photocurrent intensity versus K + concentration from 0.5 to 10 mM was obtained. 84…”
Section: Detection Of Potassium (K) Ionsmentioning
confidence: 99%
“…In addition, it is reported that the G-quadruplex can be stabilized by alkali metal cations, especially potassium ions. 15 Thus, the composition of reaction buffer should also be evaluated.…”
Section: Optimization Of Experimental Conditionsmentioning
confidence: 99%
“…3A and B. This might be due to the fact that K + could effectively stabilize G-rich oligonucleotides 15 and induce an extremely stable G-quadruplex structure when the number of G-bases is more than three, and it cannot dissociate into separate DNA strands even in the presence of target cocaine. When the G-base amount was more than ve, Gquadruplexes in buffer 1 were also very stable upon target binding.…”
Section: Optimization Of Experimental Conditionsmentioning
confidence: 99%